Musical DIAMONDS: The influence of situational classes and characteristics on music listening behavior. (November 2021) - Behbehani, Sami; Steffens, Jochen
Music listening behavior has changed significantly due to technological advancements, leading to new listening contexts in which the situational circumstances play an increased influencing role. The aim of this study was thus to investigate the relationship between situational characteristics captured by the Situational Eight DIAMONDS and psychological characteristics of music (Arousal, Valence, and Depth) people listen to in different situations. Hence, an online study was conducted, in which 198 participants described and reported on features of 3 typical, self-selected listening situations. Results suggested that individuals adapted their music listening behavior dependent on the situational characteristics reflected by the eight DIAMONDS. Furthermore, utilizing a Latent Class Analysis, we established a taxonomy of music listening situations, including positive-social, ambivalent-individual, and negative-demanding situations. Finally, both DIAMONDS and the established classes reliably predicted reported music listening behavior and therefore are recommended to be considered in future research on social and music psychology.